2015
DOI: 10.18512/1980-6477/rbms.v14n3p326-334
|View full text |Cite
|
Sign up to set email alerts
|

Aplicação de Fitorreguladores Químicos na Qualidade Tecnológica do Sorgo Sacarino cv. Biomatrix 535

Abstract: RESUMO-Este trabalho buscou avaliar a aplicação dos fitorreguladores químicos na qualidade tecnológica do sorgo sacarino. O ensaio foi realizado na Usina Cerradinho, localizada em Catanduva-SP. O delineamento experimental utilizado foi em blocos casualizados, no esquema de parcelas subdivididas, em que os tratamentos foram constituídos pela combinação de dez tratamentos envolvendo as aplicações dos fitorreguladores químicos: 5; 10; 20 g ha-1 sulfometuron-methyl; 0,10; 0,20; 0,40 L ha-1 glifosate; 0,2; 0,4; 0,8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 1 publication
4
8
0
1
Order By: Relevance
“…There was no statistical diference between doses. Audilakshmi et al (2010) and Viana et al (2015Viana et al ( , 2016 evaluating sweet sorghum hybrids obtained RS values similar to the observed in this study. Theoretically, feedstocks with high monosaccharide concentration are desirable for bioethanol industrialization, since they enhance alcoholic fermentation and partially reduce production costs associated with transport and electrical energy spent (Audilakshmi et al, 2010).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…There was no statistical diference between doses. Audilakshmi et al (2010) and Viana et al (2015Viana et al ( , 2016 evaluating sweet sorghum hybrids obtained RS values similar to the observed in this study. Theoretically, feedstocks with high monosaccharide concentration are desirable for bioethanol industrialization, since they enhance alcoholic fermentation and partially reduce production costs associated with transport and electrical energy spent (Audilakshmi et al, 2010).…”
Section: Resultssupporting
confidence: 88%
“…Assessing sweet sorghum (cv. Biomatrix 535), Viana et al (2015) reported that some methyl-sulfumeturon and glyphosate doses increased the total soluble solids content of juice, corroborating the results of this study. Otherwise, studying methylsulfumeturon effects on qualitative aspects of sweet sorghum (cv.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…4,61,62,64 Assertivamente, incrementos em açúcares teóricos recuperáveis são benéficos aos elos da cadeia sucroenergética, pois este parâmetro determina o valor pago pela matéria-prima aos produtores e permite estimar, com maior precisão, a quantidade de sacarose passível de conversão em açúcar cristal, uma das principais commodities mundiais. 67 Embora a maturação fisiológica natural de cana-de-açúcar seja capaz de propiciar razoável produtividade de ATR à cultura, esta pode ser potencializada pela ação de moléculas sintéticas com propriedades favoráveis à biossíntese de sacarose, corroborando os resultados deste estudo. 59…”
Section: Açúcares Teóricos Recuperáveis (Atr)unclassified
“…In some species, both cultivated and wild, seed treatment with phytoregulators has been effective in promoting greater expression of physiological quality, as reported by Prado Neto et al (2007) for Genipapa americana L. and by Vendruscolo et al (2016) for Solanum lycopersicum L. Phytoregulators, also called "plant bioregulators", are exogenously applied synthetic substances which alter plant morphology and physiology and may lead to qualitative and quantitative changes in agricultural production (VIANA et al, 2015).…”
Section: Introductionmentioning
confidence: 99%